Potential of Aspergillus flavus Isolated from Marginal Saline Soil as a Biofertilizer Agent: A Comparative Study with Trichoderma esperellum: Potensi Aspergillus flavus yang Diisolasi dari Tanah Salin Marginal sebagai Agen Biofertilizer: Sebuah Studi Perbandingan dengan Trichoderma esperellum - Hasanah, Risalatul; Sutarman, Sutarman (Indonesian Journal of Innovation Studies, 2023)
This study aimed to assess the potential of Aspergillus flavus, isolated from marginal saline soil, as a biofertilizer agent by comparing its in vitro diversity with the biological agent Trichoderma esperellum (collected from the UMSIDA Microbiology and Biotechnology Laboratory). The research was conducted at the Microbiology and Biotechnology Laboratory, University of Muhammadiyah Sidoarjo. Macroscopic and microscopic morphological tests were performed on Aspergillus flavus isolated from rice root soil. The sensitivity test of the biological agents on saline soil showed no influence on their growth. Notably, the findings indicated that Aspergillus flavus exhibited faster growth on saline soil compared to its growth on PDA-c media. Moreover, the combination of PDA-c and saline soil in ratios of 1:1 and 2:1 significantly enhanced the growth response of A. flavus by 50% and 70%, respectively, two days after inoculation. These results suggest the promising potential of Aspergillus flavus as a biofertilizer agent to enhance soil fertility in saline environments. Highlights: Potential of Aspergillus flavus: The study aimed to determine the potential of the fungus Aspergillus flavus, isolated from marginal saline soil, as a biofertilizer agent. The research activity included comparing its diversity in vitro with the biological agent Trichoderma esperellum. Morphological Tests: The fungus Aspergillus flavus was subjected to macroscopic and microscopic morphological tests. Morphological observations of the growth of biological agents were carried out macroscopically and microscopically. Sensitivity of Biological Agents: The test of the sensitivity of biological agents on saline soils showed no influence on the growth of biological agents on saline soil media.